2022
DOI: 10.3390/curroncol29030124
|View full text |Cite
|
Sign up to set email alerts
|

Low Platelet Count Predicts Reduced Survival in Potentially Resectable Hepatocellular Carcinoma

Abstract: The prognostic role of platelet count in hepatocellular carcinoma (HCC) remains unclear, and in fact both thrombocytopenia and thrombocytosis are reported as predictors of unfavourable outcomes. This study aimed to clarify the prognostic value of preoperative platelet count in potentially resectable HCC. We retrospectively reviewed 128 patients who underwent hepatic resection for HCC at a tertiary academic centre (2007–2019). Patient data were modelled by regression analysis, and platelet count was treated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Finally, platelets may help the liver regenerate after injury, so a low platelet count may reduce its ability to regenerate [60,61,62]. However, other studies have reported the opposite conclusion that outcomes are particularly unfavorable in people with pretreatment thrombocytosis [67]. We try to explain this seemingly contradictory result.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, platelets may help the liver regenerate after injury, so a low platelet count may reduce its ability to regenerate [60,61,62]. However, other studies have reported the opposite conclusion that outcomes are particularly unfavorable in people with pretreatment thrombocytosis [67]. We try to explain this seemingly contradictory result.…”
Section: Discussionmentioning
confidence: 94%
“…We try to explain this seemingly contradictory result. Studies found that the decrease of platelet count occurred in HCC for early small tumors, while the platelet count of patients with large tumor load in late HCC was often higher [66,67]. However, the size of the GPR value is determined by both GGT and platelet.…”
Section: Discussionmentioning
confidence: 99%
“…As already known, high GGT and AST/ALT are found to be independent factors for predicting poor overall survival of primary hepatic carcinoma patients [ 29 ].HBsAg-positive patients with HCC were also more likely to have increase transaminases and decreased platelet count as compared to HBsAg-negative patients with HCC. Decreased platelet count is link to poor survival and is a common finding in patients with advanced fibrosis and portal hypertension [ 30 ].These findings confirms the fact that most of our patients, especially those with positive HBsAg presents with hepatic decompensation and thus has a very poor overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several commonly used blood routine and biochemistry indexes have also attracted much attention from researchers in addition to the classic serum oncology biomarkers, which have the potential to serve as prospective indicators for prognosis assessment and risk stratification of patients with HCC independently or synergistically [ 27 29 ], and platelet is one of the representatives [ 11 , 30 32 ]. Studies have demonstrated that abnormal platelet counts (including thrombocytopenia and thrombocytosis) are closely related to the poor OS of patients with HCC [ 30 , 33 ]. Additionally, aberrant changes in morphology or functional status of platelet have also been discovered to be connected with tumor metastasis and patients’ adverse outcomes [ 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%